Drug Utilization Analysis in Stroke Patients at Cilacap Regional Public Hospital Using the ATC/DDD Method and DU 90% - Argi Asih; Sunarti; Khamdiyah Indah Kurniasih (Viva Medika, 2024)
Stroke is a serious medical condition in which the blood supply to the brain is disrupted, leading to the death of brain cells. The use of stroke medications aims to prevent and treat thromboembolism, and the increased use of stroke medications reflects the high global morbidity and mortality rates. This study aims to describe the utilization of drugs for stroke in patients treated at Cilacap Regional Public Hospital in 2022. The research method used was a descriptive study with a retrospective approach, referring to medical record data. A total of 167 samples were taken by purposive sampling, and the samples were evaluated using the ATC/DDD method and DU 90%. The results showed that the highest DDD/100 bed days value was for oral Acetylsalicylic Acid at 128124.19, and the lowest DDD/100 bed days value was for intravenous Phytomenadione at 6.73. The stroke medication included in the DU 90% was the ischemic stroke drug, oral Acetylsalicylic Acid, with a DU% value of 97.61%. The stroke medications in the 10% segment were the ischemic stroke drugs, namely oral Clopidogrel, oral Cilostazol, and oral Warfarin, as well as the hemorrhagic stroke drugs, intravenous Tranexamic Acid and intravenous Phytomenadione. The DDD per 100 bed days value for stroke medications exceeded the WHO's appropriateness criteria.